Terapi Komplementer Diet Nutrisi untuk Peningkatan Kadar Hb Ibu Hamil: Literature Review - Bintia, Sovia Elviana; Rahmawati, Alfiah; Wulandari, Rr.Catur Leny (REAL in Nursing Journal, 2023)
Background: Anemia is a condition in which red blood cells or hemoglobin levels decrease or are less than 11g/dl. One effort to prevent anemia in pregnant women is complementary nutritional diet therapy, namely consuming fruits and vegetables with high iron. This complementary therapy effort is able to maintain and increase red blood cells. To examine more deeply about the effect of complementary therapy on increasing hemoglobin levels in pregnant women where there is compatibility with previous studies by reviewing several studies. Methods: This review draws on several sources including systematic search studies of databases such as Google Scholar and PubMed. Search with keywords "complementary therapy", "hemoglobin level", "pregnant women". The articles obtained in a search adjusted for the title totaled 7 relevant journals. Results: The results of the 7 journal articles showed that increasing hemoglobin levels could be carried out non-pharmacologically by administering ambon bananas, guava fruit, green bean juice and honey, tomato juice, spinach and dragon fruit juice. Conclusion: The result of this literature review recommends that pregnant women consume Fe tablets together with complementary therapy to increase optimal Hb levels.Keywords: Complementary therapy,  Hemoglobin Levels, Pregnant Women